Development of game-based mini book media to improve the learning motivation of third grade students at MI - Intan Nadiroh; Amalia, Siti Choirotul; Kalimatusyaro, Mei (Mitra PGMI: Jurnal Kependidikan MI, 2025)
The use of monotonous learning modules in Indonesian language lessons results in low learning motivation of third grade students of MI Tarbiyatul Aulad. Visual learning media, such as mini books, are considered effective because they are practical and interesting. This study aims to develop and test the effectiveness of mini book media based on Game Based Learning to increase student learning motivation in Indonesian language subjects. The research method used is Research and Development (RnD) with the ADDIE model. The results showed that the development of mini book media on Energy and its Changes Information Text material, which was designed interactively with the Game Based Learning approach, was successful. This media also helps understanding the material, as evidenced by the increase in student evaluation results from 75.43% in the pre-test to 81.28% in the post-test. Student response to the mini book media is very positive, with a percentage of 90% based on the Guttman Scale, indicating that this media is very acceptable and useful.